Development of molecular techniques to identify mealybugs (Hemiptera: Pseudococcidae) of importance on grapevine in South Africa - Kruger, Kerstin (University of Pretoria, 2013)
Dissertation (Magister Scientiae)--University of Pretoria, 2007.